The mixed effects of online diversity training - Chang, Edward H; Milkman, Katherine L; Gromet, Dena M; Rebele, Robert W; Massey, Cade; Duckworth, Angela L; Grant, Adam M (Proceedings of the National Academy of Sciences - PNAS, 2019)
We present results from a large ( = 3,016) field experiment at a global organization testing whether a brief science-based online diversity training can change attitudes and behaviors toward women in the workplace. Our preregistered field experiment included an active placebo control and measured participants' attitudes and real workplace decisions up to 20 weeks postintervention. Among groups whose average untreated attitudes-whereas still supportive of women-were relatively less supportive of women than other groups, our diversity training successfully produced attitude change but not behavior change. On the other hand, our diversity training successfully generated some behavior change among groups whose average untreated attitudes were already strongly supportive of women before training. This paper extends our knowledge about the pathways to attitude and behavior change in the context of bias reduction. However, the results suggest that the one-off diversity trainings that are commonplace in organizations are unlikely to be stand-alone solutions for promoting equality in the workplace, particularly given their limited efficacy among those groups whose behaviors policymakers are most eager to influence.